Antimetastatic activity of (arene)ruthenium(II) complex of 4-aryl-4H-naphthopyran - Pracharova, Jitka; Cyrikova, Tereza; Berecka, Michal; Biersack, Bernhard; Kasparkova, Jana; Brabec, Viktor (Chemico-biological interactions, 2024)
Metastatic cancer remains a formidable challenge in anticancer therapy. Despite efforts to develop effective antimetastasis drugs over the past half-century, currently approved treatments fall short of expectations. This report highlights the promising antiproliferative activity of a ruthenium-based therapeutic agent, namely dichlorido(p-cymene)[2-amino-4-(pyridin-3-yl)-4H-benzo[h]-chromene-3-carbonitrile]ruthenium(II) (complex 1) against metastatic cell lines. Complex 1 shows significant efficacy in metastatic LoVo and Du-145 cell lines at nanomolar concentrations, being markedly more active than clinically used anticancer cisplatin. Studies on the MDA-MB-231 cell line, which displays invasive characteristics, demonstrated that 1 significantly reduces cell invasion. This efficacy was confirmed by its impact on matrix metalloproteinase production in MDA-MB-231 cells. Given that cell migration drives cancer invasion and metastasis, complex 1's effect on MDA-MB-231 cell migration was evaluated via wound healing assay and vimentin network analysis. Results indicated a strong reduction in migration. A re-adhesion assay further demonstrated that 1 significantly lowers the re-adhesion ability of MDA-MB-231 cells compared to cisplatin. To better simulate the human body environment, a 3D spheroid invasion assay was used. This method showed that 1 effectively inhibits tumor spheroids from infiltrating the surrounding extracellular matrix. This study underscores the potential of (arene)ruthenium(II) complexes with naphthopyran ligands as potent antimetastatic agents for chemotherapy.
Keywords: metastázy nádorů; proliferace buněk; Antiproliferative; Cell Line, Tumor; buněčná adheze; lidé; Antineoplastic Agents; protinádorové látky; komplexní sloučeniny; Cell Adhesion; Vimentin; pohyb buněk; Coordination Complexes; Antimetastatic; 3D spheroids; Cell Proliferation; Ruthenium; Cell Movement; Neoplasm Metastasis; nádorové buněčné linie; ruthenium; Humans